Daily Step Counts in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis of Observational Studies - Zhang, Fan; Ren, Yibo; Wang, Hui; Bai, Yan; Huang, Liuyan (Frontiers in Medicine, 2022)
Background: Physical inactivity is an essential factor in the prognosis of patients with chronic kidney disease (CKD). Daily step count is a straightforward measure to assess physical activity levels. Understanding the step counts among different CKD stages is essential to change sedentary behavior. Objectives: This systematic review and meta-analysis aimed to investigate the daily step counts in patients with CKD at a different stage. Design: A systematic review and meta-analysis. Data sources: The literature search was performed in PubMed, Embase, and Web of Science from inception to November 3rd, 2021. Review methods: Observational studies (cross-sectional, case-control, or cohort studies) reported specific values of step counts in CKD patients by the wearable device were included. A random-effects model was used to pool the data. Subgroup analysis explored differences in outcomes by stage of CKD. Heterogeneity between studies was assessed using the χ2 test of Cochrane's Q statistic. A funnel plot was conducted to investigate publication bias. Univariate and multivariate meta-regression was conducted to examine possible sources of heterogeneity Results: Twenty-eight articles were identified and used for quantitative analysis. The result showed that the daily step count in patients with CKD was 4642.47 (95% CI: 4274.18 to 5010.76), and significantly lower than the healthy population. Subgroup analysis revealed that the step counts decreased before dialysis, dropped to a freezing point at the hemodialysis phase, and increased after kidney transplantation. Meta-regression analysis showed that daily step counts were relatively higher in the Americas or younger than 60 or kidney transplant recipients. Conclusion: The status of daily step counts in patients with CKD decreases with CKD severity and increases after kidney transplantation. Although studies have begun to focus on strategies to improve step counts in patients with CKD, future studies should focus more on step counts in pre-dialysis patients and changing their physically inactive lifestyle early to alleviate deteriorating renal function.